Analysis Of The Influence Of Compensation, Leadership Style And Organizational Culture On Employee Performance In National Banking Industry - Indra Krishernawan; Donny Dharmawan; Erni Yuningsih; Loso Judijanto; Abdurohim (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
The purpose of this study is to ascertain how organizational culture and leadership style, with pay acting as an intervening variable, affect employee performance. 100 employees were used in the saturation sampling approach to determine the study's sample. Using SPSS 26, path analysis was the data analysis method employed in this investigation. The findings demonstrated tha leadership style has a direct bearing on remuneration; and organizational culture has a direct bearing on compensation. Leadership style and corporate culture have a simultaneous impact on pay. The performance of employees is directly impacted by organizational culture. Employee performance is not directly impacted by a leader's style. Compensation directly affects how well employees perform. Employee performance is influenced by salary, leadership style, and company culture all at the same time. Compensation is determined to be a mediating variable for each of the leadership style and organizational culture factors on employee performance based on the results of the Sobel Test.